Climatic Suitability for Cotton Cultivation in Iraq - Azal Ismael Khalil; khalid Akber Abdullah (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The study aimed to assess the suitability of climatic conditions for cotton cultivation in Iraq. It also aimed to identify the most suitable, least suitable, and moderately suitable regions. Methodology: The current study adopted the descriptive and analytical method to provide the necessary data for identifying the areas where cotton is cultivated. Additionally, an objective approach was used to assess the suitability of the climatic conditions for cotton cultivation in Iraq and their spatial distribution. Results: The results of the study showed that there is a compatibility between the climatic requirements and the potential of cultivation of cotton, but it varies from one station to another. The results also showed that based on the light requirements of cotton, the suitable growing period was determined for each station, with some areas being moderately and less suitable. Adequate conditions for planting, growing, and maturing cotton were found. However, rainfall varied and was erratic during the growth period. The results also revealed that the northern regions were more suitable for rainfall, particularly during the rainy season and the wind impact was light. Therefore, climatic studies are important as they help identify factors that hinder or influence agriculture, thus affecting agricultural productivity. Conclusions: It can be concluded that water consumption of cotton in Iraq increases with higher evapotranspiration rates. Evaporation rates were highest in the southern region compared to the central and northern regions due to an increase in sunshine hours, higher temperatures, and stronger winds, as well as lower relative humidity.